2022
DOI: 10.14202/vetworld.2022.1759-1764
|View full text |Cite
|
Sign up to set email alerts
|

Aerolysin gene characterization and antimicrobial resistance profile of Aeromonas hydrophila isolated from milkfish (Chanos chanos) in Gresik, Indonesia

Abstract: Background and Aim: Motile Aeromonas septicemia is a crucial disease in freshwater fish. Aeromonas hydrophila is a disease agent associated with sporadic fish mortality, food safety, and public health. This study aimed to estimate the prevalence and the presence of the aerolysin gene and antimicrobial resistance profile of A. hydrophila isolated from milkfish in Gresik, Indonesia. Materials and Methods: A total of 153 milkfish gill samples were collected from 16 locations in Gresik and then cultured and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The results showed that the number of coliforms in all samples exceeded the maximum recommended 2009). The presence of coliform and E. coli can cause health problems for consumers, especially if the meat is not cooked correctly (Fikri et al, 2022). Coliform bacteria contamination can be through the hands of the seller, unhygienic cutting so that bacteria from cutting tools can move to meat, from less sterile packaging, from water used to clean meat or cutlery which may be contaminated and from the meat itself (Collin and Huey, 2015;Dameanti et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the number of coliforms in all samples exceeded the maximum recommended 2009). The presence of coliform and E. coli can cause health problems for consumers, especially if the meat is not cooked correctly (Fikri et al, 2022). Coliform bacteria contamination can be through the hands of the seller, unhygienic cutting so that bacteria from cutting tools can move to meat, from less sterile packaging, from water used to clean meat or cutlery which may be contaminated and from the meat itself (Collin and Huey, 2015;Dameanti et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Gills in good health are bright crimson. On the contrary, unhealthy can be seen as the pale pink gills indicate anaemia, and pale tan gills indicate the production of methaemoglobin (Noga, 2010;Fikri et al, 2022). A sterile cotton bud was used to collect swab samples from the gills.…”
Section: Gill Skin and Cloacal Cavity Swab Proceduresmentioning
confidence: 99%
“…The pulse is increased moderately to around 60 beats per minute, and there may be some patchy sweating, but rectal examination is negative, and there is no diarrhea [4]. Undigestible feed can produce spasmodic colic and drastically change feeding patterns [5].…”
Section: Introductionmentioning
confidence: 99%